Fröodling av Raj- och rörsvingel i Sverige - Olofsson, Hanna; Olsson, Marcus (SLU/Agrosystems (until 121231), 2009)

(untitled)
Festulolium (Festulolium) and tall fescue (Festuca arundinacea) has not been grown in Sweden over a longer period. So far there is no greater area cultivated, but the area is increasing. Festulolium and tall fescue are expected to eventually replace meadow fescue in many leyseed mixtures to dairy cows in southern and central Sweden. Tall fescue has in recent years become popular again. Festulolium is a hybrid between ryegrass and fescue. Festulolium has high yields and good quality feed from ryegrass and good drying resistance and winterhardiness from fescue. Some festulolium varieties remind most of ryegrass, while others remind most of tall fescue. We have done a literature review and compiled the Swedish and international trials of seed cultivation of festulolium and tall fescue. We sent out a questionnaire to all growers of festulolium and tall fescue in Sweden to hear their experiences and to be able to compare their results with experimental results. Of the 20 growers we sent the questionnaire to 15 responded. The literature study showed that you got the best seed yield on clay soils if you do not have access to irrigation. A distance between rows of 24 cm is the ultimate in both conventional and organic farming and a seed amount of 8 kg/ha gave the best yield in both field trials and survey. Survey results shows that farmers add too little nitrogen to festulolium and tall fescue compared with the recommendations in the cultivation guidances and the results of field trials. Survey results shows that a well-established festulolium or tall fescue has little need of herbicides apart from the year of establishment. Results from the survey show that there is little or no attack of diseases and pests in the festulolium and tall fescue in Sweden. Growth regulation gives on average 20 % higher yield in field trials, but it is important that the crop is in good growth and not stressed by drought. Most conventional farmers growth regulated festulolium and tall fescue. If there is risk of rain, swath harvesting is not a good strategy in festulolium and tall fescue. Swath harvesting, however normally gives a higher yield but is a little more time consuming than direct harvesting. Festulolium and tall fescue appears to be a suitable crop for organic leyseed growers because the difference in the yield is small compared with conventional cultivation. We believe that there is a need for field trials with nitrogen fertilization in festulolium and tall fescue. Additionally, there is a need for field trials with growth regulation in varieties of festulolium like Felopa which has different growth characteristics than Hykor. The weakness of the thesis is that there are a limited number of growers of festulolium and tall fescue in Sweden and thus we have a rather limited number of surveys to work with.